High-strength multi-component concrete and preparation method thereof
By using modified brûlite fibers and hyperbranched polyethyleneimine in high-strength multi-component concrete, the problem of insufficient crack resistance of existing high-strength concrete is solved, and the combination of high-strength and excellent crack resistance is achieved, which significantly improves the safety performance of the building.
Patent Information
- Application Number
- CN202411557826.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-03-14
AI Technical Summary
Existing high-strength concrete has insufficient crack resistance in actual applications and is prone to cracking, resulting in building safety hazards.
A high-strength multi-component concrete is used, which includes ordinary silicate cement, polycarboxylic acid water reducer, fly ash, natural river sand, gravel, volcanic ash, basalt fibers, reinforced components and crack-resistant components. The crack-resistant properties of concrete are improved by the use of modified magnesium fibers and hyperbranched polyethyleneimine.
The compressive strength and flexural strength of concrete are improved, and the crack resistance is significantly improved, the risk of cracks is reduced, and the safety performance of the building is enhanced.
Smart Images

Figure CN119613035A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, and in particular to a high-strength multi-component concrete and a preparation method thereof. Background Art
[0002] Since the invention of cement, concrete has been widely used. Nowadays, concrete plays an important role in the process of modernization. Concrete is a material formed by mixing cement as the main gel material with coarse aggregate (crushed stone, pebbles), fine aggregate (sand), admixtures and water in proportion. As a building material, concrete is a non-combustible material with excellent fire resistance and good heat insulation and sound insulation effects. It can improve the comfort and safety of buildings. As the core material of infrastructure bridges, dams, roads, reservoirs, highways, tunnels, houses, etc., it promotes the continuous development of construction, water conservancy, transportation and other industries.
[0003] For concrete, the strength of concrete is one of the important criteria for judging the quality of concrete. In high-rise buildings and large-scale water conservancy facilities, the ordinary concrete currently used has poor aggregate quality, other impurities and unreasonable grading, resulting in low strength of concrete, which cannot improve the quality and safety of the project, and therefore cannot meet the project requirements. The existing high-strength concrete has insufficient durability and poor crack resistance, and is prone to cracking or damage. Therefore, it is very necessary to study and improve concrete. The patent with publication number CN115108775B discloses a high-strength concrete and a preparation method thereof. The concrete includes the following raw materials: cement, coarse aggregate, fine aggregate, Inorganic filler, fiber filler, modified rubber powder, water reducing agent and water are prepared by forming a premix of EVA latex powder and benzophenone, and then mixing the premix with diallyl phthalate and subjecting the mixture to irradiation treatment to form a pre-modified latex powder, which is then mixed with nano silicon dioxide and stirred to obtain modified rubber powder. The addition of the modified rubber powder enables the prepared concrete to have higher compressive strength and flexural strength, which can effectively improve the safety performance of the building. However, the patent does not take into account the importance of the crack resistance of concrete in practical applications. Poor crack resistance of concrete will lead to cracking of the concrete, and the cracks are obvious, which poses a great safety hazard to the building. Therefore, the present invention provides a high-strength multi-component concrete with high strength and excellent crack resistance. Summary of the invention
[0004] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a high-strength multi-component concrete and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A high-strength multi-component concrete comprises the following raw materials in parts by weight: 200-250 parts of ordinary Portland cement, 6-10 parts of polycarboxylate water-reducing agent, 60-80 parts of fly ash, 250-300 parts of natural river sand, 350-400 parts of crushed stone, 30-50 parts of volcanic ash, 15-20 parts of basalt fiber, 10-18 parts of reinforcing components, 10-20 parts of anti-cracking components and 150-200 parts of water.
[0006] Furthermore, the fly ash is primary fly ash or secondary fly ash; the fineness modulus of the natural river sand is 2.0-3.0; the particle size of the crushed stone is 10-20 mm; the particle size of the volcanic ash is 800-1000 mesh; the diameter of the basalt fiber is 10-20 μm and the length is 10-15 mm.
[0007] Furthermore, the preparation method of the reinforcing component comprises the following steps: Step S1: adding brucite fiber to dimethyl sulfoxide, dispersing it evenly, adding 3-chloropropyltrimethoxysilane, raising the temperature to 50-60° C., reacting for 3-5 hours, filtering, washing, and drying to obtain modified brucite fiber; Step S2: Add the modified brucite fiber into N,N-dimethylformamide, disperse it evenly, introduce nitrogen, add gellan gum and a catalyst, raise the temperature to 60-65° C., react for 4-6 hours, centrifuge, wash and dry to obtain a reinforcing component.
[0008] By adopting the above technical scheme, the hydroxyl groups on the surface of the brucite fiber can react with 3-chloropropyltrimethoxysilane, thereby introducing chlorine substituents on the surface of the brucite fiber to obtain modified brucite fiber. Under the action of a catalyst, the chlorine substituents on the surface of the modified brucite fiber can undergo a substitution reaction with the hydroxyl groups in the gellan gum structure to obtain a reinforcing component.
[0009] Furthermore, in step S1, the diameter of the brucite fiber is 0.15-16 μm, and the length is 1-3 mm.
[0010] Furthermore, in step S2, the catalyst is triethylamine or pyridine.
[0011] Furthermore, the method for preparing the anti-cracking component comprises the following steps: Step A: placing hyperbranched polyethyleneimine in tetrahydrofuran, stirring evenly, introducing nitrogen, adding p-chloromethylbenzoyl chloride, stirring and reacting at room temperature for 4-6 hours, evaporating the solvent, separating the product, and obtaining an intermediate substance; Step B: Add the intermediate material into dimethyl sulfoxide, introduce nitrogen, add glycerophosphocholine and triethylamine, stir evenly, raise the temperature to 60-70°C, react for 3-5 hours, cool to room temperature, discharge, and obtain an anti-cracking component.
[0012] By adopting the above technical scheme, a chlorine substituent is introduced into the hyperbranched polyethyleneimine structure through an amidation reaction to obtain an intermediate substance. Under the action of triethylamine, the chlorine substituent in the intermediate substance structure undergoes a substitution reaction with the hydroxyl group in the glycerophosphocholine structure to obtain an anti-cracking component.
[0013] Furthermore, in step A, the relative molecular mass of the hyperbranched polyethyleneimine is 10,000.
[0014] A method for preparing high-strength multi-component concrete comprises the following steps: Step 1: Add fly ash, natural river sand, crushed stone, volcanic ash and basalt fiber into a mixer, mix at a speed of 200-400r / min for 5-15min to obtain a mixed base material; Step 2: Mix the mixed base material with the polycarboxylate water-reducing agent, the reinforcing component, the anti-cracking component, water and ordinary Portland cement, and stir and mix at a speed of 500-800 r / min for 10-30 minutes to obtain concrete.
[0015] Beneficial effects of the present invention: (1) The brucite fiber in the reinforcing component prepared by the present invention has excellent mechanical properties. After organic modification, gellan gum is coated on the surface of the brucite fiber, the surface energy of the brucite fiber is reduced, and the brucite fiber can be evenly dispersed in the concrete, overlapped with each other, and the bonding force between the brucite fiber and the concrete aggregate is improved, filling the internal pores of the concrete. When subjected to external force, the integrity of the concrete can be better maintained, the deformation resistance of the concrete is improved, and the strength of the concrete is improved. At the same time, the gellan gum can reduce the free water in the concrete, reduce the phenomenon of bleeding and segregation, increase the lubrication effect between the fiber and the aggregate, improve the workability of the concrete, make the cement paste wrap the fiber and the aggregate more evenly, improve the homogeneity and density of the concrete, and then improve the mechanical properties of the concrete.
[0016] (2) The anti-cracking component prepared by the present invention has a hyperbranched structure. The branched chains can penetrate the gel pores and capillaries formed by cement hydration to form a network structure, fill the tiny pores inside the concrete, improve the microstructure of the concrete, and increase the density. The hyperbranched structure is also beneficial to reducing the stress concentration points inside the concrete, absorbing and dispersing external loads and internal stresses, and reducing the risk of cracks. The amide, phosphorylation choline, and ether bond hydrophilic groups form hydrogen bonds with water molecules, which have a water retention effect and reduce the amount of water evaporation, thereby reducing the plastic shrinkage force and inhibiting cracking. The introduced benzene ring and phosphorylation choline group can have a larger steric hindrance, so that the components in the concrete are more evenly dispersed, reducing the slump loss of the concrete during transportation and pouring, so that the concrete can maintain its working performance and facilitate construction operations. At the same time, it can delay the initial hydration heat of the concrete, reduce the temperature rise rate of the concrete, and reduce cracks caused by hydration heat, thereby synergistically improving the anti-cracking performance, stability and durability of the concrete from multiple angles.
[0017] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0019] Figure 1 is an infrared spectrum of the modified brucite fiber and the reinforcing component prepared in the present invention; Figure 2 It is the infrared spectrum of the anti-cracking component prepared in the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] The preparation methods of the reinforcing components and the anti-cracking components in the following embodiments and comparative examples of the present invention are as follows: 1. Preparation of reinforcing components Step S1: adding 3 g of brucite fiber with a diameter of 10 μm and a length of 1 mm into dimethyl sulfoxide, and after uniform dispersion, adding 2.1 g of 3-chloropropyltrimethoxysilane, raising the temperature to 60° C., reacting for 4 h, filtering, washing, and drying to obtain modified brucite fiber; Step S2: Add 2.8 g of modified brucite fiber to N,N-dimethylformamide, disperse evenly, introduce nitrogen, add 4.2 g of gellan gum and 2 g of triethylamine, raise the temperature to 60° C., react for 5 h, centrifuge, wash, and dry to obtain a reinforcing component.
[0022] The modified brucite fiber and reinforcing components were tested by Fourier transform infrared spectrometer, such as Figure 1 As shown, the spectral wavenumber test range is 4000cm -1 -500cm -1 , the analysis shows that in the infrared spectrum of modified brucite fiber, 3450cm -1 The absorption peak of OH in brucite fiber appeared at 1019 cm -1 The absorption peak of Si-O-Mg appeared at 696 cm -1 The absorption peak of C-Cl appeared at 602 cm -1 The absorption peak of Mg-O appeared at 1738cm -1 The absorption peak of the ester group C=O in gellan gum appeared at 1634 cm -1 The absorption peak of C=O in the main chain carboxyl group of gellan gum appears at 1095cm -1 The absorption peak of COC appeared at 696 cm -1 The absorption peak of C-Cl disappears.
[0023] 2. Preparation of anti-cracking components Step A: 3.4 g of hyperbranched polyethyleneimine with a relative molecular mass of 10,000 was placed in tetrahydrofuran, stirred evenly, introduced nitrogen, added with 0.6 g of p-chloromethylbenzoyl chloride, stirred for reaction at room temperature for 5 h, evaporated the solvent, separated the product, and obtained an intermediate substance; Step B: Add 3 g of the intermediate material into dimethyl sulfoxide, introduce nitrogen, add 1 g of glycerophosphocholine and 1.2 g of triethylamine, stir evenly, raise the temperature to 65°C, react for 5 hours, cool to room temperature, discharge, and obtain an anti-cracking component.
[0024] Fourier transform infrared spectrometer is used to carry out infrared testing on crack-resistant components, such as Figure 2 As shown, the spectral wavenumber test range is 4000cm -1 -500cm -1, analysis shows that in the infrared spectrum of the anti-cracking component, 3032cm -1 The absorption peak of CH in the benzene ring appeared at 1668 cm -1 The absorption peak of C=O in amide appeared at 1590 cm -1 The absorption peak of NH appeared at 1244 cm -1 The absorption peak of P=O appeared at 1092cm -1 The absorption peak of POC appeared at 1033 cm -1 The absorption peak of COC appeared at
[0025] Example 1 Concrete preparation Step 1: Add 6g of secondary fly ash, 25g of natural river sand with a fineness modulus of 2.6, 35g of crushed stone with a particle size of 10mm, 3g of volcanic ash with a particle size of 900 mesh, and 1.5g of basalt fiber with a diameter of 10μm and a length of 12mm into a mixer, and mix at a speed of 200r / min for 5min to obtain a mixed base material; Step 2: Mix the mixed base material with 0.6g of polycarboxylate water-reducing agent, 1g of reinforcing component, 1g of anti-cracking component, 15g of water and 20g of ordinary Portland cement, and stir and mix at a speed of 500r / min for 10min to obtain concrete.
[0026] Example 2 Concrete preparation Step 1: Add 7g of secondary fly ash, 27g of natural river sand with a fineness modulus of 2.6, 37g of crushed stone with a particle size of 10mm, 4g of volcanic ash with a particle size of 900 mesh, and 1.6g of basalt fiber with a diameter of 10μm and a length of 12mm into a mixer, and mix at a speed of 300r / min for 10min to obtain a mixed base material; Step 2: Mix the mixed base material with 0.8 g of polycarboxylate water-reducing agent, 1.4 g of reinforcing component, 1.5 g of anti-cracking component, 17 g of water and 22 g of ordinary Portland cement, and stir and mix at a speed of 600 r / min for 15 minutes to obtain concrete.
[0027] Example 3 Concrete preparation Step 1: Add 7.5g of secondary fly ash, 29g of natural river sand with a fineness modulus of 2.6, 39g of crushed stone with a particle size of 10mm, 4.5g of volcanic ash with a particle size of 900 mesh, and 1.8g of basalt fiber with a diameter of 10μm and a length of 12mm into a mixer, and mix at a speed of 350r / min for 12min to obtain a mixed base material; Step 2: Mix the mixed base material with 0.9 g of polycarboxylate water-reducing agent, 1.6 g of reinforcing component, 1.8 g of anti-cracking component, 18 g of water and 24 g of ordinary Portland cement, and stir and mix at a speed of 700 r / min for 20 minutes to obtain concrete.
[0028] Example 4 Concrete preparation Step 1: Add 8g of secondary fly ash, 30g of natural river sand with a fineness modulus of 2.6, 40g of crushed stone with a particle size of 10mm, 5g of volcanic ash with a particle size of 900 mesh, and 2g of basalt fiber with a diameter of 10μm and a length of 12mm into a mixer, and mix at a speed of 400r / min for 15min to obtain a mixed base material; Step 2: Mix the mixed base material with 1g of polycarboxylate water-reducing agent, 1.8g of reinforcing component, 2g of anti-cracking component, 20g of water and 25g of ordinary Portland cement, and stir and mix at a speed of 800r / min for 30min to obtain concrete.
[0029] Comparative Example 1 Concrete preparation Step 1: Add 7g of secondary fly ash, 27g of natural river sand with a fineness modulus of 2.6, 37g of crushed stone with a particle size of 10mm, 4g of volcanic ash with a particle size of 900 mesh, and 1.6g of basalt fiber with a diameter of 10μm and a length of 12mm into a mixer, and mix at a speed of 300r / min for 10min to obtain a mixed base material; Step 2: Mix the mixed base material with 0.8 g of polycarboxylate water-reducing agent, 1.4 g of reinforcing component, 17 g of water and 22 g of ordinary Portland cement, and stir and mix at a speed of 600 r / min for 15 minutes to obtain concrete.
[0030] Comparative Example 2 Concrete preparation Step 1: Add 7g of secondary fly ash, 27g of natural river sand with a fineness modulus of 2.6, 37g of crushed stone with a particle size of 10mm, 4g of volcanic ash with a particle size of 900 mesh, and 1.6g of volcanic fiber with a diameter of 10μm and a length of 12mm into a mixer, and mix at a speed of 300r / min for 10min to obtain a mixed base material; Step 2: Mix the mixed base material with 0.8 g of polycarboxylate water reducer, 1.5 g of anti-cracking component, 17 g of water and 22 g of ordinary Portland cement, and stir and mix at a speed of 600 r / min for 15 minutes to obtain concrete.
[0031] Comparative Example 3 Concrete preparation Step 1: Add 7g of secondary fly ash, 27g of natural river sand with a fineness modulus of 2.6, 37g of crushed stone with a particle size of 10mm, 4g of volcanic ash with a particle size of 900 mesh, and 1.6g of basalt fiber with a diameter of 10μm and a length of 12mm into a mixer, and mix at a speed of 300r / min for 10min to obtain a mixed base material; Step 2: Mix the mixed base material with 0.8 g of polycarboxylate water reducer, 1.4 g of brucite fiber, 1.5 g of anti-cracking component, 17 g of water and 22 g of ordinary Portland cement, and stir and mix at a speed of 600 r / min for 15 minutes to obtain concrete.
[0032] Comparative Example 4 Concrete preparation Step 1: Add 7g of secondary fly ash, 27g of natural river sand with a fineness modulus of 2.6, 37g of crushed stone with a particle size of 10mm, 4g of volcanic ash with a particle size of 900 mesh, and 1.6g of basalt fiber with a diameter of 10μm and a length of 12mm into a mixer, and mix at a speed of 300r / min for 10min to obtain a mixed base material; Step 2: Mix the mixed base material with 0.8 g of polycarboxylate water-reducing agent, 1.4 g of reinforcing component, 1.5 g of hyperbranched polyethyleneimine, 17 g of water and 22 g of ordinary Portland cement, and stir and mix at a speed of 600 r / min for 15 minutes to obtain concrete.
[0033] Performance Testing The concrete prepared in Examples 1 to 4 and Comparative Examples 1 to 4 was made into samples that met the test standards. After curing for 28 days, the compressive strength and splitting tensile strength of the samples were tested in accordance with the standard GB / T 50081-2019. According to the standard GB / T 50082-2009, the shrinkage rate of the samples was tested after curing for 3 days and 60 days to judge the crack resistance. The test results are shown in the following table: From the analysis of the above table, it can be seen that the concrete prepared by Examples 1 to 4 of the present invention has the advantages of high strength and good crack resistance, among which Example 2 shows the best test effect. Comparative Example 1 adds a reinforcing component, and the compressive strength and splitting tensile strength test results are excellent. No anti-cracking component is added, and the shrinkage test result is poor; Comparative Example 2 adds an anti-cracking component, and the shrinkage test result is excellent. No reinforcing component is added, and the compressive strength and splitting tensile strength test results are poor. It is impossible to use gellan gum to coat brucite fiber to enhance the strength of concrete and improve the homogeneity and compactness of concrete, and enhance Concrete strength; Comparative Example 3 added unmodified brucite fiber, the surface energy was extremely large, it was difficult to disperse evenly in the concrete, the effect of enhancing the strength of the concrete was poor, the compressive strength and splitting tensile strength test results were poor, and the anti-cracking component was added, and the shrinkage test result was good; Comparative Example 4 added a reinforcing component and a hyperbranched polyethyleneimine, and the plastic shrinkage force could not be reduced by the water retention effect of the hydrophilic group. The steric hindrance of the benzene ring and phosphorylcholine was used to delay the initial hydration heat of the concrete and reduce the risk of cracks. The shrinkage test results were poor, and the compressive strength and splitting tensile strength test results were good.
[0034] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A high-strength multi-component concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 200-250 parts of ordinary Portland cement, 6-10 parts of polycarboxylate water reducer, 60-80 parts of fly ash, 250-300 parts of natural river sand, 350-400 parts of crushed stone, 30-50 parts of volcanic ash, 15-20 parts of basalt fiber, 10-18 parts of reinforcing component, 10-20 parts of anti-cracking component and 150-200 parts of water.
2. A high-strength multi-component concrete according to claim 1, characterized in that: The fly ash is primary fly ash or secondary fly ash; the fineness modulus of the natural river sand is 2.0-3.0; the particle size of the crushed stone is 10-20 mm; the particle size of the volcanic ash is 800-1000 mesh; the diameter of the basalt fiber is 10-20 μm, and the length is 10-15 mm.
3. The high-strength multi-component concrete according to claim 1, characterized in that: The preparation method of the reinforcing component comprises the following steps: Step S1: adding brucite fiber to dimethyl sulfoxide, dispersing it evenly, adding 3-chloropropyltrimethoxysilane, raising the temperature to 50-60° C., reacting for 3-5 hours, filtering, washing, and drying to obtain modified brucite fiber; Step S2: Add the modified brucite fiber into N,N-dimethylformamide, disperse it evenly, introduce nitrogen, add gellan gum and a catalyst, raise the temperature to 60-65° C., react for 4-6 hours, centrifuge, wash and dry to obtain a reinforcing component.
4. The high-strength multi-component concrete according to claim 3, characterized in that: In step S1, the diameter of the brucite fiber is 0.15-16 μm and the length is 1-3 mm.
5. The high-strength multi-component concrete according to claim 3, characterized in that: In step S2, the catalyst is triethylamine or pyridine.
6. The high-strength multi-component concrete according to claim 1, characterized in that: The preparation method of the anti-cracking component comprises the following steps: Step A: placing hyperbranched polyethyleneimine in tetrahydrofuran, stirring evenly, introducing nitrogen, adding p-chloromethylbenzoyl chloride, stirring and reacting at room temperature for 4-6 hours, evaporating the solvent, separating the product, and obtaining an intermediate substance; Step B: Add the intermediate material into dimethyl sulfoxide, introduce nitrogen, add glycerophosphocholine and triethylamine, stir evenly, raise the temperature to 60-70°C, react for 3-5 hours, cool to room temperature, discharge, and obtain an anti-cracking component.
7. The high-strength multi-component concrete according to claim 6, characterized in that: In step A, the relative molecular mass of the hyperbranched polyethyleneimine is 10,000.
8. A method for preparing high-strength multi-component concrete as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Add fly ash, natural river sand, crushed stone, volcanic ash and basalt fiber into a mixer, mix at a rate of 200-400r / min for 5-15min to obtain a mixed base material; Step 2: Mix the mixed base material with the polycarboxylate water-reducing agent, the reinforcing component, the anti-cracking component, water and ordinary Portland cement, and stir and mix at a speed of 500-800 r / min for 10-30 minutes to obtain concrete.
Citation Information
Patent Citations
A high-strength concrete and its preparation method
CN115108775B